Cosmosiin Increases ADAM10 Expression via Mechanisms Involving 5’UTR and PI3K Signaling - Min, Zhuo; Tang, Ying; Hu, Xiao-Tong; Zhu, Bing-Lin; Ma, Yuan-Lin; Zha, Jing-Si; Deng, Xiao-Juan; Yan, Zhen; Chen, Guo-Jun (Frontiers in Molecular Neuroscience, 2018)
The α-secretase “a disintegrin and metalloproteinase domain-containing protein” (ADAM10) is involved in the processing of amyloid precursor protein (APP). Up-regulation of ADAM10 precludes the generation of neurotoxic β-amyloid protein (Aβ) and represents a plausible therapeutic strategy for Alzheimer’s disease (AD). To explore the potential compounds that could promote ADAM10 expression, we have performed high-throughput small-molecule screening in SH-SY5Y (human neuroblastoma) cells that stably expressed luciferase reporter gene driven by ADAM10 promoter, in which 5-untranslated region (5’UTR) was included. This has led to the discovery of cosmosiin (apigenin 7-O-β-glucoside). Here we report that in human cell lines (SH-SY5Y and HEK293), cosmosiin proportionally increased the immature and mature forms of ADAM10 protein, without altering mRNA level. This effect was attenuated by translation inhibitors or by deleting 5’UTR of ADAM10, suggesting a translational mechanism. Further luciferase assay revealed that the first 144 nucleotides of 5’UTR were necessary to mediate cosmosiin enhancement of ADAM10 activity in SH-SY5Y cells. Accordingly, cosmosiin failed to increase ADAM10 protein in murine cells, which lack native expression of the ADAM10 transcript with the 5’UTR element identified. The potential signaling pathway might involve PI3K, as pharmacological inhibition of PI3K attenuated cosmosiin effect on ADAM10 protein. Finally, cosmosiin attenuated endogenous Aβ generation as Aβ40/42 level was significantly reduced. Collectively, the first 144 nucleotides of 5’UTR and PI3K signaling were involved in cosmosiin enhancement of ADAM10 protein. These results suggested that cosmosiin exhibits a therapeutic potential for AD.